Improving MSMEs Performance Through Digitalization of Business Products in Micro Business Groups in Motoboi Kecil Village, Kotamobagu City, North Sulawesi - Soegoto, Agus Supandi; Wenas, Rudy Steven; Wahab; Soeikromo, Deasy; Soegoto, Andini Pratiwi; Satria, Andi Wiratama (LP2M of Institute for Research and Community Services - UIN Walisongo, 2024)
MSMEs play an important role in national economic resilience because they can become independent businesses that can increase people's income and welfare. On the other hand, fierce competition in today's digital era has encouraged the community and MSMEs business actors. Advances in internet technology and digitalization have become solutions for business development and efforts to expand the market. This community service aims to: 1) introduce good MSME business planning and management, and 2) improve MSME business management skills through digital technology. PKM activities were carried out in Motoboi Kecil village, Kotamobagu City. The results of the activity showed that the participants' ability to plan and implement the business increased, as well as participants were able to understand and use digital technology, as a means of promoting their products on social media, increasing sales and business profits of MSMEs.